2001
DOI: 10.1603/0022-0493-94.4.935
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering Cost Associated with Resistance to Transgenic Cotton in the Pink Bollworm (Lepidoptera: Gelechiidae)

Abstract: Fitness costs associated with resistance to transgenic crops producing toxins from Bacillus thuringiensis (Bt) may have important effects on the evolution of resistance. We investigated overwintering costs in pink bollworm, Pectinophora gosypiella (Saunders), strains with different degrees of resistance to Bt cotton. Frequency of resistant individuals in a strain was not associated with induction of diapause or emergence from diapause in early winter. Emergence from diapause in the spring was 71% lower in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 32 publications
4
76
0
3
Order By: Relevance
“…Plutella xylostella fed on a diet containing Bt laid fewer eggs with lower viability, had reduced larval survival and adult eclosion rates, and ultimately reduced fecundity [38,39]. Carriere et al [40] reported that resistance to Cry1Ac in Pectinophora gossypiella was associated with over-wintering fitness costs. Other pest species have also been reported to develop Bt resistance under the continuous selection pressure of the Bt toxin [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…Plutella xylostella fed on a diet containing Bt laid fewer eggs with lower viability, had reduced larval survival and adult eclosion rates, and ultimately reduced fecundity [38,39]. Carriere et al [40] reported that resistance to Cry1Ac in Pectinophora gossypiella was associated with over-wintering fitness costs. Other pest species have also been reported to develop Bt resistance under the continuous selection pressure of the Bt toxin [2,34].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides no information about the life history traits potentially altered by the presence of this allele. Based on previous studies, the traits affected may be as different as overwintering success (Carrière et al, 2001b), fecundity and mating success (Groeters et al, 1994), larval survival , maternal effects (Carrière et al, 2001a) and first-male paternity (Higginson et al, 2005). Génissel et al (2003a) pointed out that Bt resistance allele frequencies exceeding 10 À3 may result from a combination of a high mutation rate (eg u ¼ 10 À5 ) and a small (eg s ¼ 0.01) and/or recessive (eg h ¼ 0.1) fitness cost.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, we distributed the effect of the overwintering cost equally among generations, assuming five generations of pink bollworm per year (17). In field experiments, the mean overwintering cost was 71% (30). This cost reflects an overwintering survival ratio of 0.29 for the resistant strain relative to the susceptible strain.…”
Section: Methodsmentioning
confidence: 99%
“…Although resistant strains were fixed or nearly fixed for RR, some susceptible strains used in fitness cost comparisons were heterogeneous, which could cause underestimation of fitness costs (30,31,33). The presence of RS or SS individuals in resistant strains could cause overestimation of effects of incomplete resistance because RS and SS perform better on non-Bt cotton than on Bt cotton.…”
Section: Methodsmentioning
confidence: 99%